OpenStudy (anonymous):

10x^2-3x-1=0

5 years ago
OpenStudy (anonymous):

10x^2-3x-1 = 0 We can factor this either as (10x +/- ?)(x +/- ?) or (5x +/- ?)(2x +/- ?) Since the 'factors' of 1 are... 1, and the value in the middle is 3, I'm going to go with the second set of factors. This means (5x + 1)(2x - 1) = 0 (we can check this using the FOIL method, which shows 5x*2x + 2x + -5x + -1 = 10x^2 -3x -1) If you need to find the zeros, we break the factors apart and set each of them equal to 0. 5x + 1 = 0 5x = -1 x = -1/5 2x - 1 = 0 2x = 1 x = 1/2

5 years ago
OpenStudy (anonymous):

Thanks

5 years ago
OpenStudy (anonymous):

You're very welcome!

5 years ago